Assessment of the test‐retest reliability of human gingival blood flow measurements by Laser Speckle Contrast Imaging in a healthy cohort. (9th February 2018) - Molnár, Eszter; Fazekas, Réka; Lohinai, Zsolt; Tóth, Zsuzsanna; Vág, János
Abstract: Objective: The reliability of gingival blood flow measured by Laser Speckle Contrast Imaging is unknown. Our aim was to investigate the effect of factors inherent in oral mucosa measurement on intra‐day and inter‐day reliability. Methods: Gingival blood flow was measured in seventy healthy subjects. First, measurements were obtained by varying the incidence angle of imaging, using a lip retractor. Second, 3 snapshots were taken with closure of the mouth in‐between, and lips were retracted by a dental mirror. These were repeated 1 week later. Third, snapshots were taken either by direct view or using a mirror. Reliability was assessed based on coefficient of variation. Results: Unlike retraction of the lips and the mirror, the incidence angle had an effect on mean blood flow. The coefficient of variation within a subject was 6.4% with the mouth constantly open. With retraction, the intra‐session, and the inter‐day coefficient of variation were 8.3% and 10.5%, respectively. The coefficient of variation was 11.9% by alternating direct and indirect imaging. Conclusions: Laser Speckle Contrast Imaging has good short‐ and long‐term reliability regardless of lip retraction or an indirect view. This technique seems to be appropriate for the long‐term clinical non‐invasive follow‐up of gingival microcirculation.